Cataract awareness program: improving cataract prevention knowledge and behavior in the elderly - Tri Damayanty Syamsul; Asma Juita Syam; Ridwan Ridwan; Kasmawati Kasmawati; Sudirman Sudirman (Edukasi Ilmiah Indonesia, 2026)
Cataract remains one of the leading causes of avoidable visual impairment among older adults, particularly in community and rural settings where awareness and access to eye health services are limited. Low levels of knowledge, misconceptions that cataract is a normal and untreatable part of aging, and delayed health-seeking behaviour contribute to late diagnosis and preventable blindness. This community service program aimed to improve knowledge, awareness, and preventive behaviour regarding cataract among older adults through a community-based educational intervention using a field visit approach. The program was conducted in a selected community and involved older adult participants recruited with the support of local leaders. Activities were conducted in a single-day session and included structured health education on cataract, interactive discussions, basic health assessments, and free eye examinations. Educational materials covered the definition of cataract, risk factors such as smoking, ultraviolet exposure, and chronic diseases, early signs and symptoms, preventive measures, and available treatment options. The interactive discussion allowed participants to clarify misconceptions and relate the information to their personal experiences. The results showed a clear improvement in participants’ knowledge levels after the intervention, with a marked shift from low to moderate and reasonable knowledge categories. Participants also demonstrated increased awareness of the importance of early detection and regular eye examinations. The integration of education with basic health and eye screening enhanced participant engagement and reinforced the relevance of eye health within overall healthy aging. This program demonstrates that community-based cataract education using a field visit approach is a practical and effective strategy to strengthen eye health literacy among older adults and supports efforts to prevent avoidable visual impairment at the community level